Hemostasis Technique Using an Adjustable Nylon Tie in Dog with Splenic Hematoma and Lymphoid Hyperplasia - dos Santos, Ivan Felismino Chagas; Del Poente, Maria Duarte; Bombrini, Giovanna Cristina; Gomes, Mayara Viana Freire; da Silva, Bruna Martins; Rahal, Sheila Canevese; Tannus, Filipe Carrari Isaac; de Góis, Frederico Matheus Ducatti; de Azevedo, Maria Gabriela Picelli (Acta Scientiae Veterinariae, 2017)
Background: Splenic hematoma is an encapsulated blood accumulation, which is macroscopically indistinguishable from malignant spleen. The treatment of choice and final diagnosis were by splenectomy and exploratory laparotomy followed by biopsy and histopathological examination, respectively. Nylon tie bands are devices made of polyamide 6.6, same material of surgical nylon wires, and has been used in different surgical procedures in animals. The present report case aimed to describe the use of nylon tie bands polyamide 6.6 in a 2.3-year-old Golden retriever dog diagnosed with splenic hematoma and lymphoid hyperplasia; and the clinical presentation, diagnostic evaluation, histological diagnosis of splenic hematoma and lymphoid hyperplasia. Case: A 2.3-year-old intact male Golden retriever dog was presented with history of anorexia, apathy, regurgitation and weight loss. During the physical examination was identified a mass in the left side of abdomen. The complete blood count (CBC), serum biochemistry, urinalysis, and thoracic radiographs were no alteration. Abdominal ultrasound revealed splenomegaly and heterogeneous hypoechoic structure. Splenectomy using an adjustable nylon ties polyamide 6.6 for hemostasis technique was performed during an exploratory laparotomy. The spleen presented hematoma and lymphoid hyperplasia at the histopathological examination, as well as the presence of siderocalcinotic plate in the trabecular spleen. The dog presented with no regurgitation, apathy or anorexia after 10 days of surgery. CBC, serum biochemistry analysis, thoracic radiographs and abdominal ultrasound revealed no abnormalities. Video laparoscopy did not showed any sign of adherence on the local where used the nylon tie bands. One year and three months after the surgery, the owner was contacted by telephone, since he had changed to other city, and he reported that the dog was healthy without any clinical signs. Discussion: The present case report describes the using of nylon tie polyamide 6.6 bands in a 2.3-year-old Golden retriever dog diagnosed with splenic hematoma and lymphoid hyperplasia. According to the author’s knowledge, the present case is the first report regarding to using nylon tie bands in splenectomy, and clinical characteristics of hematoma and lymphoid hyperplasia in young dog. The adjustable nylon tie bands allowed a secure and faster ligature when compared with traditional nylon surgical suture wires in different surgical procedures in animals and humans patients, and was considered well tolerated and non-toxic. Reports concerning to complications to the use of nylon tie in veterinary surgery were present in the literature. Otherwise, these complications were related to surgical technique failure and inadequate aseptic technique; inadequate use of nylon tie bands before assigning it as a hemostatic material. Partial splenectomy is recommended for treatment of splenic hematoma and lymphoid hyperplasia in dogs whenever possible; however, the macroscopic findings concerning splenic disorders are not enough to set the distinction between benign and malignant disorders. Clinical sign associated with splenic disorders in the present case was abdominal distension due to hematoma and nodular lymphoid hyperplasia. An adjustable nylon tie polyamide 6.6 band can be used to clamp the spleen vessels, gastroepiploic artery, gastric artery and omento veins.